Design and fabricating sequential control based automatic sweet potato stick machine - Jajang Jaenudin; Tedy Rahman; Edilla; Tianur (JTTM : Jurnal Terapan Teknik Mesin, 2025)
Currently, one of the significant challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the food processing sector is enhancing both efficiency and effectiveness, particularly in the production of sweet potato sticks, commonly known as "tela-tela." This issue is exacerbated by low productivity rates and the inherent risks associated with manual cutting methods, which can lead to inconsistencies and safety hazards. In this article, we introduce a newly developed automatic machine designed specifically for the efficient production of sweet potato sticks. The development process involved several key stages: system design, mechanical system design, control system design, and the integration of these systems into a cohesive unit. The core components of the control system include a relay, a proximity sensor that acts as a material detector to ensure the sweet potatoes are accurately positioned for cutting, and a 1-phase AC motor equipped with a gear mechanism that drives the sweet potatoes toward a specialized stick-shaped cutter. Experimental results indicate that the machine can achieve a production rate of approximately 23.34 kg per hour with a commendable success rate of about 82.82%. Furthermore, the control system operates flawlessly, maintaining a 100% operational efficiency during testing. These results reflect a significant improvement and position this machine as a competitive alternative compared to existing options in the market, showcasing potential for widespread application in the MSME sector